ANALISIS MEDIA PEMBELAJARAN IPAS PADA MATERI PESAWAT SEDERHANA BAGI SISWA SEKOLAH DASAR - Melinda Syahputri; Sella Hardi Yanti; Nurul Hasanah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the use of social science learning media for simple machines in fourth-grade students at SDN 050695 Batang Serangan. The background of this study stems from students' poor understanding of abstract concepts in social science, particularly in simple machines, which require a visual approach and real-world practice. The problem examined is the effectiveness of learning media in improving students' understanding of the material. This study used a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. The results indicate that concrete learning media, such as teaching aids and simple models, can increase student interest in learning, conceptual understanding, and active participation during the learning process. The learning media proved relevant and appropriate to the learning characteristics of elementary school-aged children. Based on these findings, it is recommended that teachers consistently use engaging and appropriate media in social science learning, and that the school support this by providing adequate learning resources. This research makes an important contribution to the development of more effective social science learning strategies in elementary schools.